Hepatocyte-specific PKCβ deficiency protects against high-fat diet-induced nonalcoholic hepatic steatosis - Yaoling Shu; Faizule Hassan; Vincenzo Coppola; Kedryn K. Baskin; Xianlin Han; Neil K. Mehta; Michael C. Ostrowski; Kamal D. Mehta (Elsevier, 2021)
Objective: Nonalcoholic hepatic steatosis, also known as fatty liver, is a uniform response of the liver to hyperlipidic-hypercaloric diet intake. However, the post-ingestive signals and mechanistic processes driving hepatic steatosis are not well understood. Emerging data demonstrate that protein kinase C beta (PKCβ), a lipid-sensitive kinase, plays a critical role in energy metabolism and adaptation to environmental and nutritional stimuli. Despite its powerful effect on glucose and lipid metabolism, knowledge of the physiological roles of hepatic PKCβ in energy homeostasis is limited. Methods: The floxed-PKCβ and hepatocyte-specific PKCβ-deficient mouse models were generated to study the in vivo role of hepatocyte PKCβ on diet-induced hepatic steatosis, lipid metabolism, and mitochondrial function. Results: We report that hepatocyte-specific PKCβ deficiency protects mice from development of hepatic steatosis induced by high-fat diet, without affecting body weight gain. This protection is associated with attenuation of SREBP-1c transactivation and improved hepatic mitochondrial respiratory chain. Lipidomic analysis identified significant increases in the critical mitochondrial inner membrane lipid, cardiolipin, in PKCβ-deficient livers compared to control. Moreover, hepatocyte PKCβ deficiency had no significant effect on either hepatic or whole-body insulin sensitivity supporting dissociation between hepatic steatosis and insulin resistance. Conclusions: The above data indicate that hepatocyte PKCβ is a key focus of dietary lipid perception and is essential for efficient storage of dietary lipids in liver largely through coordinating energy utilization and lipogenesis during post-prandial period. These results highlight the importance of hepatic PKCβ as a drug target for obesity-associated nonalcoholic hepatic steatosis.